Measuring the Effectiveness of Autonomous Network Functions that Use Artificial Intelligence Algorithms - Narayanan, Premnath K.; Harrison, David K. (Nordic and Baltic Journal of Information & Communications Technologies, 2021)
Autonomous network functions such as Software Defined Networks (SDN), Self-Organizing Networks (SON), and virtual function network orchestrator plays a crucial role in 5G and beyond 5G wireless telecommunication network. Advancements in Artificial Intelligence (AI), Machine Learning (ML) algorithms, and frameworks have led to adequate adaption of stochastic algorithms for autonomous network functions, aimed at performing better than human capability. Measuring the effectiveness of such autonomous network functions is a challenge since stochastic algorithms are fundamentally generalized models and could potentially make malicious proposals. Traditionally effectiveness of network is measured through network assurance Key Performance Indicators (KPIs). Autonomous network functions are kept active when the KPIs are in the acceptable limit, and the network is showing improvement over time. This paper introduces • Factors that are to be considered beyond KPIs for effective measurement of autonomous network functions that use stochastic algorithms. • Adopting the right scales for measuring the effectiveness of autonomous network functions using the grading system from medical practices which are used for the treatment of critical illness.